Evaluation of the effectiveness of the Global Medical Student Partnership program in undergraduate medical education - Samuels, Hannah; Rojas-Luengas, Vanessa; Zereshkian, Arman; Deng, Shirley; Moodie, Jenna; Veinot, Paula; Bowry, Ashna; Law, Marcus (Canadian Medical Education Journal, 2020)
Background: The Global Medical Student Partnership (GMSP) is, a medical student-led international initiative to promote accessible Global Health learning. This study aims to evaluate the effectiveness of the GMSP program in meeting its learning objectives. Methods: Canadian and international medical student pairs met online monthly (January-May 2018) to discuss global health-related medical cases. Students then reviewed cases with local GMSP peers and faculty experts. A mixed-methods study was performed to evaluate whether the objectives of the program had been achieved. 26 of 32 (81.3%) students completed a questionnaire, and 13 (40.6%) also participated in one-on-one semi-structured interviews. Descriptive statistics and thematic analysis were used to analyze students’ perspectives on skill development through GMSP. Results: GMSP students agreed or strongly agreed that international collaboration and communication skills were more important to them following program participation (92.3%, 92.3% respectively). Many expressed that after GMSP, they knew more about their healthcare system, practices abroad and how to solve complex health issues (92.3%, 84.6%, 61.5% respectively). Qualitative data showed GMSP improved students’ communication and presentation skills, provided a foundation for international relationships, fostered appraisal of diverse health systems, and furthered students’ understanding of health advocacy. Conclusions: Our findings demonstrate that GMSP met its original objectives by providing students with opportunities to engage in international collaborations and to further develop their skills in advocacy, communication, and health-systems research. This program may be an important addition to medical education as it makes use of technology and peer-to-peer exchange to enable global health learning.